Effectiveness of azvudine versus nirmatrelvir/ritonavir for hospitalized patients with SARS-CoV-2 infection and pre-existing liver diseases - Guanyue Su; Feng Gao; Mengzhao Yang; Ling Wang; Lili Liang; Silin Li; Guangming Li; Na Han; Guotao Li; Guowu Qian; Shixi Zhang; Hong Luo; et al. (Virology Journal)
Abstract Background Azvudine and nirmatrelvir/ritonavir are recommended as priority treatments for SARS-CoV-2 infection in China, but their effectiveness and safety in patients with pre-existing chronic liver diseases remains unknown. Methods We conducted a multicenter retrospective cohort study of hospitalized SARS-CoV-2 infected patients with chronic liver diseases in ten hospitals of Henan Province. Azvudine recipients were 2:1 propensity score matched with nirmatrelvir/ritonavir recipients. Efficacy and safety were evaluated by Kaplan–Meier analysis, multivariable Cox regression model, subgroup analysis, as well as sensitivity analyses. Results Among 37606 hospitalized patients infected with SARS-CoV-2, 1355 azvudine recipients and 373 nirmatrelvir/ritonavir recipients met the inclusion criteria. Patients with azvudine treatment showed comparable effectiveness to nirmatrelvir/ritonavir with regard to both all-cause death (P = 0.34) and composite disease progression (P = 0.32), even after adjusting for other covariates (all-cause death: HR: 0.80, 95%CI: 0.574-1.128; composite disease progression: HR: 1.31, 95%CI: 0.999-1.723). Notably, compared with nirmatrelvir/ritonavir, azvudine showed better effectiveness for patients with a comorbidity of primary malignant tumor in reducing all-cause death. Four sensitivity analyses further confirmed the robustness. Conclusions The effectiveness of azvudine may potentially comparable to nirmatrelvir/ritonavir in SARS-CoV-2 infected patients with pre-existing liver diseases with respect to all-cause death and composite disease progression, without serious safety concerns. Due to the existence of potential biases, further studies still need to evaluate the efficacy of these two drugs. Trial registration The trial was retrospectively registered at ClinicalTrials.gov (CT.gov identifier: NCT06349655).